Analisis Kinerja Kemandirian Keuangan UKM dan Aktivitas Produksi Produk Olahan Ikan pada UD. Permata Indah Situbondo Dengan Metode Actyvity Based Costing (ABC) - Ratnaning Tyasasih; Triska Dewi Pramitasari (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2019)
The purpose of this study is to analyze the performance of financial independence and SME production activities. Data analysis methods include the calculation of COGS using Activity Based Costing (ABC), production activity analysis and SME financial independence analysis. The results showed that the calculation of COGS was more accurate using the ABC method, where 3 products (jerky, petis and shredded fish) were undercosting, while 3 other products (chips, crackers and anchovies) were overcosting. The results of the SME production activity analysis are greater than the industry activity standard ratio where the total value of assets turnover is 3x (> 2x) and accounts receivable turnover is 16x (> 15x). The results of the analysis of the level of financial independence of SMEs have the value of the profitability of assets and the profitability of their own capital greater than 10 (measurement standards) and the value of the operational independence of SMEs greater than 100 (measurement standards). So it can be concluded that UD. Permata Indah is a healthy, effective and financially independent SME